Clinical Neurological and Immunological Features of Vascular Seizures in Hemorrhagic Stroke (Eurasian Medical Research Periodical, 2022)
This is due to the etiological, pathogenetic and clinical heterogeneity of ischemic stroke, as well as the presence of patients with concomitant diseases that aggravate the course of stroke and prevent the directed action of neuroprotective agents. Stroke is one of the leading causes of seizures in adults. The study of factors included screening surgery, the risk of early and late post-stroke epileptic seizures, and a study of 300 patients aged 41- 94 years. Data were studied on disease history and neuroimaging. This study was conducted on the basis of statistical data showing an increased risk of early epileptic seizures with hemorrhagic stroke